Design of Compact Dual-band PIFA Antenna for 5G Communication Systems - Huỳnh Nguyễn Bảo Phương; Đặng Thị Từ Mỹ (My University, 2023)
Design of Compact Dual-band PIFA Antenna for 5G Communication Systems
Keywords: Ăng-ten 5G; PIFA Antenna; Thiết kế ăng-ten